Professor Richard Carter (1945–2021). Issue 1 (January 2022) - Alano, Pietro; Culleton, Richard; Doerig, Christian; Miller, Louis
Abstract : The malaria research community lost a pioneer when Professor Richard Carter passed away at the age of 76 on 4 September 2021. Richard was an exceptionally brilliant malariologist, always inquisitive and gifted with an unorthodox way of thinking.